A review exploring the adsorptive removal of organic micropollutants on tailored hierarchical carbon nanotubes. Issue 4 (21st April 2021) - Alayan, Haiyam Mohammed; Aljumaily, Mustafa Mohammed; Alsaadi, Mohammed Abdulhakim; Mjalli, Farouq Sabri; Hashim, Mohd Ali
Abstract: Compared to other existing carbon nanomaterials (CNMs), carbon nanotubes (CNTs) are recognized for their significant properties. Despite their strong adsorption affinity, the difficulty of their dispersion and separation leads to limit their application in practical water treatment. Moreover, wastewater contamination by noxious organics, such as bisphenol A (BPA) and methylene blue (MB) dye compounds has become a world-wide environmental concern because they may be harmful to humans' health and the ecosystem. Therefore, this article aims to explore the potential of economically directly growing CNTs on porous supports, such as the powder activated carbon (AC) to develop a multiscale hybridized material and to investigate their expected potential as viable adsorbents for removing persistent organic contaminants.